Bronislaw ZaJeski about the Conspiracies of the XIX century in Lithuania and Belarus - Caban, Wieslaw (Respectus Philologicus, 2004)
The problem of independence movements among young Poles, Lithuanians and Belarusians in the 1830s and 1840s has not been discussed in depth yet. The leading role in initiating independence fights can be ascribed to Polish youths studying in Dorpat who, additionally, tried to establish contacts with their peers living in Lithuania and Belarus. The members of independence movement had substantially different attitudes. Some of them, being under the influence of the Great Emigration, were ready for immediate military action; others (among them Bronisław Zaleski) were convinced that if military actions happened too early, they would only result in further repressions. At the same time the issue concerning the character of relationship between independent Poland, Lithuania and Belarus became a pending one. All those young people engaged in the movement of independence were arrested and sent to prison.
Keywords: conspiratorial parties in Lithuania and Belarus; Tsardom's policy towards internal independence movement; repressions towards Polish youth studying in Dorpat and Vilnius